Analysis of the cultivation of medical students by calligraphy education—taking traditional Chinese medicine acupuncture and traditional Chinese medicine orthopedics as example - Zhang Yu; Zhang Heng; Wu XinYi (Journal of Exploration of Vocational Education, 2025)
In recent years, medical higher education institutions have actively followed the 《National Guidelines for Public Art Courses in Ordinary Colleges and Universities》 to offer art courses, aiming to implement aesthetic education. Calligraphy class is an important component of art courses. Calligraphy education is of great significance in improving the humanistic literacy of medical students, inspiring their innovation ability, enhancing their philosophical thinking, and many other aspects. Hippocrates once said that medicine is both a science and an art. Calligraphy is a shining pearl in the field of art. Conducting calligraphy education in medical higher education institutions not only teaches medical students how to write, but also enhances their understanding of medical philosophy and methodology. As a "stone from another mountain", calligraphy can guide medical students’ clinical practice and continuously improve clinical diagnosis and treatment effectiveness.